2018
DOI: 10.2500/aap.2018.39.4135
|View full text |Cite
|
Sign up to set email alerts
|

Differences in cytokine levels between the nasal polyps of adolescents with local allergic and adolescents with allergic or nonallergic rhinitis

Abstract: Results of our study indicated that RANTES may play an important role and contribute to allergic reaction in LAR, and RANTES may be related to the pathogenesis of LAR.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…Although IL-5 and RANTES could be increased in AR, it was not directly related to nNO, so measurement of cytokine and chemokine in nasal secretion is helpful for the evaluation of AR, but it would be difficult to use as an indirect method of evaluation of nNO. 22 Arnal et al 18 showed that nNO production increased regardless of the presence or absence of symptoms in AR due to the persistent inflammatory response of the nasal mucosa. However, it has been reported that nNO levels can be reduced when symptoms are severe and long-lasting.…”
Section: Discussionmentioning
confidence: 99%
“…Although IL-5 and RANTES could be increased in AR, it was not directly related to nNO, so measurement of cytokine and chemokine in nasal secretion is helpful for the evaluation of AR, but it would be difficult to use as an indirect method of evaluation of nNO. 22 Arnal et al 18 showed that nNO production increased regardless of the presence or absence of symptoms in AR due to the persistent inflammatory response of the nasal mucosa. However, it has been reported that nNO levels can be reduced when symptoms are severe and long-lasting.…”
Section: Discussionmentioning
confidence: 99%
“…Presence of allergic rhinitis (AR) was evaluated in all enrolled patients at the beginning of the study on the basis of clinical symptoms, a sufficiently high total IgE serum concentration, and positivity in a skin prick (SPT) or serum allergen test, such as ImmunoCAP system. 10,11 Patients with a positive SPT (wheal diameter !3 mm larger than that of negative control after 15 min) and high titer (!2 positivity; !0.70 IU/ml) of IgE antibodies specific for at least one antigen were diagnosed with AR. All enrolled subjects were evaluated with respect to the eosinophilic cationic protein (ECP) level and eosinophil number.…”
Section: Study Participantsmentioning
confidence: 99%
“…Its pathogenesis is largely unknown. In this issue, Choi et al 12 evaluated the cytokine profile of nasal polyps derived from adolescents with LAR in comparison with the cytokine profile of nasal polyps derived from adolescents with either allergic or nonallergic rhinitis. The authors performed immunoassays by using polyp tissue homogenates to quantify the levels of RANTES (regulated on activation of normal T-cell expressed and secreted), tumor necrosis factor alpha, interleukin 5, and sera to assess total IgE and eosinophil cationic protein values.…”
mentioning
confidence: 99%